IMPLEMENTASI KEBIJAKAN REKTOR TENTANG TATA KRAMA DAN ETIKA MAHASISWA DI UKM/ORMAWA UNIVERSITAS NEGERI PADANG - Ningrum, Nillam Martha Sonia; Khaidir, Afriva; Alhadi, Zikri (JPSI (Journal of Public Sector Innovations), 2019)
This study aims to determine the implementation of Rector's policy on student's etiquette and ethics in Student Activity Units or Student Organization (UKM/Ormawa) Padang State University (UNP) based on Circular Letter Number 3916/UN35/KM/2017. The background of this research because there are still some points in the circular that did not happen like the activities of students until the night, making the secretariat as a place to sleep, and the safety and cleanliness of PKM that has not been awake. This research is a qualitative research using descriptive method. The informant of this research is Vice Rector III UNP as the maker of SE No.3916/UN35/KM/2017, Vice Dean III Faculty of Social Sciences, Kabag. Student Affairs and alumnus, Kasubbag. MPIK's Student Affairs, UKM Coach, Security Guard, BEM and MPM, some UKM/Ormawa managers UNP environment, students and communities living around UNP who can provide information. Techniques and data collection tools in this study using interview techniques, observation and documentation studies. In the data collection used research instruments in the form of interview guides, observation format and documentation study format. In this study the data analyzed obtained from interviews and interpreted qualitatively, in the form of abstraction, words and statements. The result of the research shows that the implementation of Rector's policy on students' etiquette and ethics in UKM/Ormawa UNP is good enough with the form of control that is done related to the etiquette and ethics in the student organization at UNP only still need improvement on the policy that has been implemented. Constraints encountered in the implementation of SE No.3916/UN35/KM/2017, among others, still low understanding and awareness of the contents of the policy, facilities and infrastructure are still inadequate, less assertive sanctions given to violators and still lack of supervision from the Rector and other related parties. From the results of this study the researchers provide advice to the parties involved, including to the Rector of UNP as policy makers maintain communication, coordination and good cooperation with each element, and for the implementation of the policy firmly need a rule of law is stronger than the circular, so also with the students and coaches UKM/Ormawa Coach to always direct and supervise the activities of students to be more directed and orderly. In addition, there must be full security and supervision from the security guard and the community around UNP, as well as students and UKM/Ormawa there must be understanding and awareness of existing regulations to be more sensitive to a policy so that the implementation of Rector policy can run optimally.